Electric Poling and Relaxation Studies of PMMA Thin Films Containing Diaminopyrazole Derivatives as Dipolar Chromophores - Arora, Sanjiv; Kumar, Sushil (Journal of Research Updates in Polymer Science, 2013)
Vacuum-deposited thin films of polymethylmethacrylate (PMMA) doped by varying concentrations (2-10 % by weight of polymer) of some 3,5-diaminopyrazole derivatives as dipolar chromophores were prepared to study their relaxation behaviour . Poling of thin films was carried out using multi-point corona-poling technique to orient dipolar chromophores in proper aligned position. Poling and depoling behaviours of these thin films have been investigated by UV/Vis absorption spectra. For each chromophore, poling efficiency was found to increase with poling voltage as well as poling temperature up to a certain limit retaining the properties of thin films. Maximum value of concentration dependent order parameter was obtained at temperature slightly lower than glass transition temperatures of corresponding guest-host matrices. After 300 hrs. of poling under the conditions (5 kV, near Tg, 30 min.), the decayed amounts of order parameters at room temperature were within the range 25-38 % of the initial value for various guest-host systems. Relaxation behaviour of poling-induced chromophore alignment has also been studied at elevated temperature.